Diversity of fish in Kuala Langsa Waters Langsa City - Razi, Fakhrur; Isma, Muhammad Fauzan; Febri, Suri Purnama; Putriningtias, Andika (Universitas Malikussaleh, 2025)
The purpose of this study was to identify the diversity of fish species based on the waters in Kuala Langsa Village and provide outputs in the form of water conditions in Kuala Langsa Village. Fish sampling was carried out using the Purposive Sampling method. The composition of fish species caught at the three stations consisted of 12 species, namely: Mystus nemerus, Channa striata, Chanos chanos, Drepane punctate, Stolephorus sp, Gerres erythourus, Leiognathus splendens, Lutjanus johnii, Planiliza subviridis, Johnius belangerii, Epinephelus sp., Terapon jarbua. The total number of fish caught at station I was 36 fish, station II was 22 fish, and station III was 28 fish. Total relative abundance at stations I, II, and III in Kuala Langsa Kota waters obtained the highest abundance of fish from the species Leiognathus splendens with a value of 31.40% while the lowest relative abundance was found in the species Epinephelus sp and Chanos with a value of 1.16%. The diversity index at stations I, II, III ranged from 1.73 to 2.19. The three stations had moderate diversity criteria, indicating that the biological condition and fish diversity were still stable. Uniformity values of stations I, II, III, range from 1.53-1.59 which indicates high uniformity. This is due to the high uniformity because the fish population is spread evenly at each station. Dominance values at stations I, II, III range from 0.14-0.24 indicating low dominance or no fish species dominating at each station. Keywords: Diversity; Dominance; Kuala Langsa; Relative abundance; Uniformity